An exploratory study into the experiences and challenges of founders of non-profit organisation in the Western Cape with specific reference to fundraising - Schuller, Raymond (Department of Social Development, 2023)
New Non-profit Organisations (NPOs) are being registered daily. They are established by passionate individuals committed to providing critical services in support of the national development agenda and the global Sustainable Development Goals (SDGs). They therefore form an integral part of a broader ecosystem to ensure a just, equitable and fair society. Unlike for-profit enterprises, donor funding constitutes the single largest source of income for most NPOs. Because of the high levels of donor dependency by many NPOs, fundraising becomes critical and very often the most challenging activity for many NPOs. Given the fundraising challenges and volatile, uncertain, complex and ambiguous (VUCA) environments in which NPOs operate, this exploratory research study reflects on the motivations why founders of NPOs based in the Western Cape started NPOs and their experience and challenges with respect to sustaining these organisations. In particular, it explores: • The main motivations and rationale by founders to start NPOs; • The fundraising experience of founders; • The extent to which founders of NPOs prioritised fundraising; and • How the fundraising role and practice evolved over time The study examined several texts on the motivation and fundraising experience of founders of NPOs as part of a literature review. The research question and methodology is based on this literature review. Non-probability purposive sampling was used for this research study. Twenty founders of NPOs based in the Western Cape participated in the study using a semistructured interview schedule. Ethics clearance for the study was received from the University of Cape Town, Department of Social Development. The dissertation expands on existing knowledge regarding motivations for registering NPOs and the levels of personal investment required by founders. It makes a number of findings with the respect to fundraising as a strategic competency and the importance of fundraising capability. The study confirms that very few founders have prior fundraising and NPO experience and that fundraising is not significantly prioritised as a strategic imperative. I intend for some of the findings to serve as guidance to individuals planning to start a new NPO, of the important role of fundraising which can ultimately ensure the long-term sustainability of the organisation they plan to launch. The research study concludes with a set of recommendations prospective founders could consider when contemplating starting a new NPO.